(untitled) (Jurnal Teknologi Industri Pertanian, 2022)
Grapes are a commodity that has high added value. The wide variety of products shows that wine has a high demand. This study aimed to provide recommendations for alternative priority products for processed Balinese grapes and optimization strategies in the development of processed grape products in Buleleng Regency. The research method was a survey, observation, focus group discussion, mapping of industrial trees, and Analytic Hierarchy Process (AHP). The results showed that there were 10 existing processed products, and there were 19 processed products as alternatives. The priority processed products were wine, jam, and syrup. Matrix internal external showed a hold and maintains strategy with an alternative strategy of diversifying wine products by looking at consumer preferences, producing fine quality and high yield wine, entering the international market, installing pipes to drain water throughout the vineyards, making grape derivative products as unique as possible, training the labour about wine good production methods, reducing the number of sales of fresh grapes, increasing the production of processed grapes for sale, maximizing the promotion of processed wine, forming a market for processed wine products through cooperation with companies, governments, and universities, providing labour about marketing, and forming the institutional structure of the grapes. The priorities of the proposed strategies were training the labour about marketing, entering the international market, and reducing the number of sales of fresh grapes. Keywords: alternative strategies, grapes, industry, processed products